Proceso de atención de enfermería en paciente con neumonía del lobulo inferior izquierdo en el Hospital Luis Vernaza en la ciudad de Guayaquil - Zambrano Terán, Alba María (2018)
Lobular pneumonia is an infection that attacks a single lobe or section of a single lung, which is frequently due to Streptococcus pneumoniae. The most frequent causes of pneumonia are caused by bacteria and viruses, while the less frequent causes are caused by fungi and parasites. The aim of the clinical case is to apply the Nursing Care Process to an adult patient with a medical diagnosis of Lower Left Lobe Pneumonia, hospitalized in the Internal Medicine area of the Luis Vernaza Hospital in the city of Guayaquil, which was fully complied with. Thanks to this case we were able to conclude that the nursing care process is fundamental to provide quality care to adults with pneumonia, in order to reduce the long hospital stages due to this pathology, improving their sanitary conditions and a considerable improvement of the manifestations clinics, through a high degree of interactions and patient participation, being the most relevant medical treatment and nursing interventions performed, are key to its early recovery. When developing the nursing care process, we were able to know and adapt to the realization of this necessary and timely tool, which serves us in our future life as a Bachelor of Nursing.